Kolaborasi Mahasiswa KKN UINSU Bersama Kader Posyandu dalam upaya Pencegahan Stunting melalui Program Edukasi di Desa Tambun Sungkean, Samosir Sumatera Utara - Rani Suraya; Afriani Harahap; Tri Anggraini; Muhammad Riyan Ramadhan (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
Stunting is a chronic nutritional problem that remains a public health challenge in Indonesia, including in Samosir Regency, North Sumatra. The Community Service Program (KKN) of the State Islamic University of North Sumatra (UINSU) collaborated with Posyandu cadres in Tambun Sungkean Village to prevent stunting through a participatory education program. Implementation methods included anthropometric measurements, providing nutritious food made from local ingredients, and counseling on parenting and balanced nutrition for mothers of toddlers. The results of the activity showed that optimizing the role of Posyandu not only improved monitoring of child growth and development but also strengthened community awareness of the importance of nutrition and parenting. Education based on nutritious cooking demonstrations and the use of local foods was able to change the perception of mothers of toddlers that healthy food does not have to be expensive. Furthermore, the nutrition awareness community movement succeeded in increasing maternal participation in Posyandu activities and routine counseling. Thus, the collaboration between KKN students and Posyandu cadres has proven effective in fostering collective awareness and serving as a model for community-based interventions that support strategies to accelerate stunting reduction at the village level.